REDISTRIBUTION - Robin Boadway; Michael Keen (Queen's University, Department of Economics, 1999)
This paper, prepared for the Handbook of Income Distribution (edited by A.B. Atkinson and F. Bourguignon), reviews some of the central issues that arise in thinking about the motives for, politics of, constraints on and measurement of, redistribution. Amongst the themes are: the potential usefulness of apparently inefficient policy instruments in overcoming the self-selection constraints on redistribution and limiting the damage that ill-intentioned policymakers can do; the continued (perhaps increased) ignorance as to the effective incidence of many key taxes and benefits; and, while there are circumstances in which redistribution may plausibly generate efficiency gains, the likelihood that some trade-off between equity and efficiency is inescapable.
Keywords: D3; D6; D7; H2; I3; 330; Redistribution; Inequality